The interaction of social networks with the earthquake disaster of February 6, 2023 and the role of counseling intervention in treating post-traumatic stress disorder in individuals (A survey on individuals’ adaptation and social resilience within the com - البيرق علي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Natural disasters are a phenomenon accompanying human life anywhere and anytime, and this makes thinking focused on pre-preparing for them and adaptation is that dynamic phenomenon or process by which a person aims to modify his behavior, in order to be more adapted to the environment in which he lives, when an individual is surprised by a dangerous and unexpected circumstance that we see that he is going through moments that disasters must leave a psychological and social impact on an individual’s life، A devastating earthquake struck Syria on February 6, 2023, killing and injuring thousands of Syrians. This tragic event has aggravated the difficult situation faced by the Syrian people and caused widespread destruction and material damage. Thus, the earthquake aggravated the socio-economic challenges in society, which led to an increase in inflation and unemployment. This study delves into the socio-economic impact of the earthquake on the Syrian population. PTSD is only a psychological effect of the imbalance caused by it in psychological adaptation, which requires clinical treatment, guidance and family guidance, especially in children, which contributes to achieving the child’s adaptation to the urge to alleviate its symptoms such as cognitive change and avoidance behavior, and even cure them completely, which achieves a social situation adapted to the traumatic event, especially in earthquake cases, where anxiety and frustration are also present as a manifestation of maladaptation Despite the fact that what man has become demanded in the theory of the social role and the division of Labor is much further from achieving his human perfection, the most important thing is to achieve what his social role requires.